P29 Acute Respiratory Assessment Service (ARAS): A New Nurse-Led Service Managing Patients with Acute Respiratory Conditions in Secondary and Primary Care. (19th November 2012) - Prakash, A; Win, S; Thompson, J; Cummings, H; Bell, A; Kastelik, JA; Morjaria, JB
Abstract : Background: Acute respiratory disorders are a huge burden to acute medical services in any healthcare system. Our institution has two large teaching hospitals providing care to a population of over 600, 000 people; a mixture of inner city and rural areas. Aim: A retrospective review of outcomes of a new nurse-led specialist respiratory assessment service supported by respiratory consultants for the management of acutely unwell respiratory patients. Methods: We developed the ARAS team consisting of 3 specialist respiratory nurses supervised by 2 consultant respiratory physicians. The ARAS team reviewed all acute respiratory admissions, twice daily, to the acute medical specialist unit. They assessed in-patients on medical wards and intensive care, and provided early community discharge reviews. The ARAS team worked with community-based respiratory, oxygen, dietician and smoking cessation services. Results: Over 9 months (November 2010 to July 2011), a total of 813 patients were managed through ARAS; 446 (54.9%) COPD, 77 (9.5%) asthma, 111 (13.7%) pneumonia, 90 (11.1%) lower respiratory tract infection (LRTI), and 89 (10.9%) with other respiratory conditions. More than half (52.4%) of the patients admitted were discharged within 96 hours. There were 254 (31.2%) patients who had supported discharges, of which 153 (60.2%) were discharged within 96 hours. Early supported discharges (<96 hours) were mainly for patients with COPD (124 (81.0%)) and asthma (23 (15.0%)). The 30-day readmissions were 122 (15% of total), of which 10.2% and <1% of all ARAS-reviewed patients had COPD and asthma, respectively. Conclusion: A dedicated specialist service provides high standard of care for patients with acute respiratory disorders and a link between the acute hospital and community services resulting in a reduced length of hospital stay with reasonably low re-admission rates in an area in the UK with high prevalence of respiratory disorders.